Post-exposure HIV prophylaxis adherence to full 28-day course versus weekly therapy in Tehran - Abbasian, Ladan; Rezaee, Sahar; Alavian, Golbarg; SeyedAlinaghi, SeyedAhmad; Alipour, Abbas; Dehghan Manshadi, Seyed Ali; Hosseinpoor, Hossein; Mohraz, Minoo (HIV & AIDS review, 2024)
Background This randomized clinical study was conducted to compare the adherence of post-exposure human immunodeficiency virus (HIV) prophylaxis (PEP) in full 28-day course of antiretroviral (ARV) treatment versus weekly therapy, and to find reasons for insufficient compliance among people referred to HIV clinic of Imam Khomeini Hospital, a teaching, and referral university hospital in Tehran, from 2018 to 2019. Material and methods This study determined the most suitable PEP protocol between full 28-day and weekly courses. After obtaining informed consent from 293 participants with exposure to HIV (both sexual and non-sexual), 106 and 111 individuals were randomly divided into two groups of a 28-day course and weekly PEP protocol, respectively, by simple randomization method, and the remaining 76 persons were lost to follow-up during the study. Adherence to PEP was defined as taking 95% of the prescribed antiretroviral therapy (ART) in each group. Chi-square test (Fisher exact test) and t-test were performed using SPSS software considering other variables, including age, gender, marital status, educational level, occupation, and distance from work or residence to a hospital. Results After analyzing data and possible factors affecting treatment adherence, it was found that 28-day PEP protocol increased ARV compliance (OR = 4.14; 95% CI: 1.79-9.58%; p = 0.001) compared with weekly protocol. Furthermore, no associations between adherence and demographic characteristics, such as gender, age, education level, occupation, income, marital status, and factors, including distance from people's place of residence or work, were found. Conclusions Adherence to PEP was much higher in the 28-day protocol than the weekly course of treatment.